vertex (-1,5); point (2,-4)

f( X) = K ( X +1 )

^{2 }+ 5 -4 = K ( 3 )

^{2}+ 5- 9 = K ( 9)

K = -1

f( X) = - ( X + 1 )

^{2 }+ 5 = - X

^{2 }- 2X +4-
CREATE FREE ACCOUNT Access thousands of free resources from expert tutorsComment on posts and interact with the authorsAsk questions and get free answers from tutorsView videos, take interactive quizzes, and more!
- Become a Student
- Become a Student
- Sign In

vertex (-1,5); point (2,-4)

Tutors, please sign in to answer this question.

f( X) = K ( X +1 ) ^{2 } + 5

-4 = K ( 3 )^{2} + 5

- 9 = K ( 9)

K = -1

f( X) = - ( X + 1 ) ^{2 }+ 5

= - X^{2 }- 2X +4

Mark B.

Passionate and Patient American Sign Language Tutor

Linden, NJ

5.0
(37 ratings)

CAROLE C.

Experienced Tutor and Certified College Adviser

Montclair, NJ

4.9
(325 ratings)

Yayoi K.

Top Rated MCAT, DAT, Biology, Chemistry and Physics Tutor

East Brunswick, NJ

4.9
(37 ratings)